TRADISI DO’A PADANG PADA MASYARAKAT KECAMATAN KUANTAN HILIR KABUPATEN KUANTAN SINGINGI - Thun Fatikhah Thun Fatikhah; Isjoni Isjoni '; Tugiman Tugiman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Tradition Do'a Padang is a tradition that practiced Kuantan Hilir District at the time of going down to the farm or starting farming season. Tradition is a custom that handed down from generation to generation by our ancestors to the next generation and are still ongoing in community. Tradition inseparable from culture, because the culture's value system is the highest level and most abstract of cultural. The purpose of this study was to know what it was tradition Do’a Padang for the community Kuantan Hilir District, to find out how the implementation of tradition Do’a Padang in the district of Kuantan Hilir, to know the values contained in the tradition of Do’a Padang of the community of the District of Kuantan Hilir, to find out what any changing and the changing factors in the tradition of Do’a Padang on the community of Kuantan Hilir District. The method used is descriptive qualitative method, where data were collected through interviews, observation, documentation, and the school library. Data was analyzed using qualitative methods. This study began since submission the title of proposal until the writer completed of the final review report. The result of studies show that tradition Do’a Padang is still exist until now days. With development of make tradition of Do’a Padang suffered some changing on the implementation procedures, values the cultural and social life. The changing in the tradition of Do’a Padang it self caused by modernization and social change. Based on these results it can be concluded that the tradition of Do’a Padang is a origanal tradition of District Kuantan Hilir community that has been around since the forefathers and the community of Kuantan Hilir trying to keep this tradition continued until the next generation.Keywords: Tradition, Do’a Padang, Kuantan Hilir